Does Organizational-Professional Conflict Affect the Turnover Intention: Examining the Mediating Roles of Job Performance and Job Burnout - Latrivita Sejanni Sinaga; Gatot Imam Nugroho (President University Press, 2017)
Turnover intention is one of the most critical problem in every public accounting firm. A high auditor turnover will certainly give negative impact on the accounting firms. The antecedents of a high turnover intention are important to know in order to minimize the auditor turnover and prevent the possibility losses which will be gained by the accounting firms. This research is purposed to examine the effect of organizational-professional conflict toward turnover intentions and the role of job performance and job burnout as the mediating variables. Since the variables of this research is unobservable variable, structural equation modelling partial least squares (SEM-PLS) with WarpPLS 3.0 software is used as the statistical analysis method of this research. The data is collected using questionnaire with responses of 150 auditors from 17 public accounting firms in Jakarta. The results indicate that organizational-professional conflict significantly and negatively affects job performance, and organizational-professional conflict also found significantly and positively affects job burnout. Job performance is found to insignificantly and positively affect turnover intentions, while job burnout significantly and positively affects turnover intentions. In addition, it is also found that the relationship between organizational-professional conflict and turnover intentions is fully mediated by job performance and job burnout.